Sensory dimensions of peach-palm fruit (Bactris gasipaes) and implications for future genetics = Dimensiones sensoriales del chontaduro (Bactris gasipaes) e implicaciones para su futura investigación genética - Martínez Rioja, Jose María
Introduction. Long-term genetic improvement efforts in Latin America aimed to ameliorate peach-palm fruit farmers' technical capacities and livelihoods have proven to be ineffective. Although experts agree this is partly the result of large uncertainty regarding consumer preferences, such research remains as virtually nonexistent. Objective. To identify chemical and morphologic attributes that are attractive for final consumers of peach-palm fruit and how these attributes are related to final perceptions of fruit quality, through statistical and econometric methods. Materials and methods. By using the harvest from a large set of varieties from a peach-palm (Bactris gasipaes) germplasm bank in Southwestern Colombia, 482 evaluations were made between April to October of 2016 by local consumers who tasted the fruits and gave a report on their perception of taste/quality in a case study scheme. Combining these data with further information on fruit color, oiliness perception, and additional controls, an ordered logit regression model was set to identify the attributes that describe peach-palm fruits with the most favorable scores for their taste/quality perception. Results. Preferences on oil contents were not linear. Fruits perceived as high-oil were between 9 and 13 % more likely to be considered as having the best taste/quality, while those perceived high-starch content were correlated with a significant aversion towards the fruit, namely 43 % less likely to be among the best fruits. Conclusion. A great deal of research is yet to be done around peach-palm fruit consumer preferences and, furthermore, it should be carried on an interdisciplinary ground. Further analyses of desired fruit traits should be made at sub-national levels, identifying ranges of suitable oiliness and morphological expected attributes and how available genetic material could help to satisfy those needs.